Genomic insights into Dactylosporangium sp. AC04546, a rubber degrader with three latex clearing proteins - Basik, Ann Anni; Gibu, Namiko; Kawagiwa, Yukimura; Ng, Siuk-Mun; Yeo, Tiong Chia; Sudesh, Kumar; Kasai, Daisuke (Frontiers in Microbiology, 2024)
With more than 100 rubber-degrading strains being reported, only 9 Lcp proteins isolated from Nocardia, Gordonia, Streptomyces, Rhodococcus, Actinoplanes, and Solimonas have been purified and biochemically characterized. A new strain, Dactylosporangium sp. AC04546 (strain JCM34239), isolated from soil samples collected in Sarawak Forest, was able to grow and utilize natural or synthetic rubber as the sole carbon source. Complete genome of Strain AC04546 was obtained from the hybrid assembly of PacBio Sequel II and Illumina MiSeq. Strain AC04546 has a large circular genome of 13.08 Mb with a G+C content of 72.1%. The genome contains 11,865 protein-coding sequences with 3 latex clearing protein (lcp) genes located on its chromosome. The genetic organization of the lcp gene cluster is similar to two other reported rubber-degrading strains—Actinoplanes sp. OR16 and Streptomyces sp. CFMR 7. All 3 Lcp from strain AC04546 were expressed in Escherichia coli and exhibited degrading activity against natural rubber. The distinctiveness of strain AC04546, along with other characterized rubber-degrading strains, is reported here.